2021
DOI: 10.1038/s41398-021-01552-y
|View full text |Cite
|
Sign up to set email alerts
|

Emotional adaptation during a crisis: decline in anxiety and depression after the initial weeks of COVID-19 in the United States

Abstract: Crises such as the COVID-19 pandemic are known to exacerbate depression and anxiety, though their temporal trajectories remain under-investigated. The present study aims to investigate fluctuations in depression and anxiety using the COVID-19 pandemic as a model crisis. A total of 1512 adults living in the United States enrolled in this online study beginning April 2, 2020 and were assessed weekly for 10 weeks (until June 4, 2020). We measured depression and anxiety using the Zung Self-Rating Depression scale … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
22
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 33 publications
3
22
1
Order By: Relevance
“…Aligning with our sample-wide findings, studies of general North American samples (e.g., Asmundson & Taylor, 2020 ; Shuster et al, 2021 ) found higher anxiety scores in May 2020 relative to subsequent pandemic assessment timepoints, and previous research by Yildirim et al (2021) demonstrated increased anxiety symptoms in cancer patients during the pandemic relative to before. Fear of cancer recurrence may not have increased overall in the present sample because current participants had completed primary cancer treatment several years prior to the pandemic, reducing the salience of recurrence risk, and the pandemic did not present new cancer recurrence risks.…”
Section: Discussionsupporting
confidence: 88%
“…Aligning with our sample-wide findings, studies of general North American samples (e.g., Asmundson & Taylor, 2020 ; Shuster et al, 2021 ) found higher anxiety scores in May 2020 relative to subsequent pandemic assessment timepoints, and previous research by Yildirim et al (2021) demonstrated increased anxiety symptoms in cancer patients during the pandemic relative to before. Fear of cancer recurrence may not have increased overall in the present sample because current participants had completed primary cancer treatment several years prior to the pandemic, reducing the salience of recurrence risk, and the pandemic did not present new cancer recurrence risks.…”
Section: Discussionsupporting
confidence: 88%
“…Our findings were consistent with theirs in that they reported that female gender, younger age, and lower household income were associated with increased depression across time. They also found that worsening economic situation due to COVID-19 was associated with increased depression over time ( 32 ). The most recent longitudinal study of which we are aware measured depressive symptoms over the previous 7 days using the PHQ-2 with the last reporting period being from 20 January to 1 February 2021 ( 10 ).…”
Section: Discussionmentioning
confidence: 99%
“…Of the longitudinal studies conducted at the start of the COVID-19 pandemic, findings suggested no change or a slight decline in depressive symptoms during the first half of 2020 ( 30 33 ). For example, Shuster et al ( 32 ) found that anxiety and depressive symptoms declined after the initial weeks of COVID-19, measured between April 2020 and June 2020. Their study differs from ours in that the population was not representative of U.S. adults, captured a 10-week span (relative to our 12-month comparison), and may have seen a decline in depressive symptoms due to loss to follow-up of persons with depression and seasonal effects, with affect improving during summer months.…”
Section: Discussionmentioning
confidence: 99%
“…Ó 2021 The Author(s). Distributed as a Hogrefe OpenMind article under the license CC BY-NC-ND 4.0 (https://creativecommons.org/licenses/by-nc-nd/4.0) Shuster et al, 2021) and underscore the importance of targeting support (prevention and treatment) to individuals with one or even more of these risk factors (e.g., mothers of young children with low income; cf. Brakemeier et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In reviewing studies analyzing longitudinal data during the pandemic (see ), it is striking that some studies report no change (Bendau, Plag, et al, 2021; Groarke et al, 2021), and other studies even report a decrease (Fancourt et al, 2021; Varga et al, 2021) in depressive and anxiety symptomatology. Inline, a study of more than 1,500 participants from the United States which examined longitudinal changes in depression and anxiety weekly from April to June 2020 also found that depression and anxiety scores were high in early April but decreased over time (Shuster et al, 2021). Notably, this study and all our selected studies identified in the databases were restricted to the first lockdown and the following months until summer 2020.…”
Section: Discussionmentioning
confidence: 99%